A difference without as such. Derrida and his difference with Heidegger - Trujillo, Iván (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
In an attempt to contribute to the debates on the relationship between both Derrida’s and Heidegger’s thoughts, we advance here that any initiative to interpret the relationship between them should take into consideration the fact that Derrida himself affirms to explicate himself with Heidegger. Also, to explicate oneself with the other seems to be considered by Derrida as a general structure of the relations between thoughts in the history of Philosophy. Inasmuch as this more general structure is itself what makes is it impossible to state these relations in oppositional terms, this concerns above all Hegel. Furthermore, inasmuch as this impossibility is itself what takes place in a history of Philosophy signed by the value of presence, Hegel only appears as the one who takes this value up to its most unavoidable and compelling point. To recognize this compelling force, and the way it hasn’t stopped to organize the history of Metaphysics, concerns both Heidegger’s and Derrida’s thoughts of difference.
Keywords: Hegel; Heidegger; ghost; difference; presence